Education for patients with limb loss or absence: Aging, overuse concerns, and patient treatment knowledge gaps - Finnie, Dawn; Griffin, Joan M.; Kennedy, Cassie C.; Schaepe, Karen; Boehmer, Kasey; Hargraves, Ian; Amer, Hatem; Jowsey-Gregoire, Sheila (Frontiers in Psychology, 2022)
The goals of vascular composite allotransplantation (VCA) for hand are to maximize functional status and psychosocial wellbeing and to improve quality of life. Candidates are carefully vetted by transplant programs through an extensive evaluation process to exclude those patients with contraindications and to select those that are most likely to attain functional or quality of life benefit from transplant. Patient choice for any treatment, however, requires that candidates be able to understand the risks, benefits, and alternatives before choosing to proceed. This study aimed to understand patients’ knowledge and perceptions about treatment options for hand loss, including hand transplant. This study will be used to inform a standardized education approach and develop conversation aids for use by clinicians and patients throughout the treatment decision process. Ten individuals who had experienced hand amputation or had congenital limb loss were interviewed to better understand previous and current decisions about treatment, experiences in adjusting to their treatment, and perceptions about hand VCA. From this qualitative interview data, four findings emerged: 1) knowledge and education around VCA as a treatment option; 2) adaptation of individuals with limb loss; 3) fear of risk associated with transplantation; 4) issues of aging and overuse injuries to existing limbs Results suggests that there is opportunity for expanding education about all treatment options for patients with new loss, long-term loss, and congenital limb loss. Establishing a baseline of knowledge about all options – prosthetics, rehabilitative strategies, and VCA—can help patients evaluate their values and goals of treatment. Issues associated with aging, including overuse and injury, and adaptability over the life course should be included in considerations about treatment choices. Data indicate the need for routinely assessing patient preferences about treatment choice so patients can plan for their future as they adapt and age and as technology for treatments change. To assure that thorough information is provided for current and future decision-making, education about treatment choices and selection procedures for VCA should be standardized.